2019
DOI: 10.1126/sciadv.aau8462
|View full text |Cite
|
Sign up to set email alerts
|

Does the U.S. public support using gene drives in agriculture? And what do they want to know?

Abstract: Gene drive development is progressing more rapidly than our understanding of public values toward these technologies. We analyze a statistically representative survey (n = 1018) of U.S. adult attitudes toward agricultural gene drives. When informed about potential risks, benefits, and two previously researched applications, respondents’ support/opposition depends heavily (+22%/−19%) on whether spread of drives can be limited, non-native versus native species are targeted (+12%/−9%), or the drive replaces versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 50 publications
(89 reference statements)
2
40
0
Order By: Relevance
“…A recent study from Mali, for instance, reveals the reluctance of community members to accept experimental releases of genetically modified mosquitoes in their villages, arguing that the technology should be first tried elsewhere to show evidence of safety [62]. A recent US study has shown that nearly two-thirds of respondents trusted universities and the department of agriculture (but not the private sector or the Department of Defence) to develop gene drives [63]. This study further attests to the importance of gaining approval from local scientists, and the need to strengthen communication between scientists and communities in deliberating over the appropriateness of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Mali, for instance, reveals the reluctance of community members to accept experimental releases of genetically modified mosquitoes in their villages, arguing that the technology should be first tried elsewhere to show evidence of safety [62]. A recent US study has shown that nearly two-thirds of respondents trusted universities and the department of agriculture (but not the private sector or the Department of Defence) to develop gene drives [63]. This study further attests to the importance of gaining approval from local scientists, and the need to strengthen communication between scientists and communities in deliberating over the appropriateness of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Mali, for instance, reveals the reluctance of community members to accept experimental releases of genetically modified mosquitoes in their villages, arguing that the technology should be first tried elsewhere to show evidence of safety [64]. A recent US study has shown that nearly two thirds of respondents trusted universities and the department of agriculture (but not the private sector or the Department of Defence) to develop gene drives [65]. This study further attests to the importance of gaining approval from local scientists, and the need to strengthen communication between scientists and communities in deliberating over the appropriateness of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional work is needed to determine the mode of action of spore killers and/or other similar meiotic drives for scientific as well as regulatory reasons. Although the technology undoubtedly involves the release of a genetically modified organism, the potentially transformative impact of this type of technology, should at least be investigated further with appropriate regulation, alongside studies to gauge social acceptance and safety of such technologies (Jones et al, 2019).…”
Section: Discussionmentioning
confidence: 99%